Different architectures to develop repetitive controllers. Issue 1 (July 2017) - Sanz i López, Víctor; Costa-Castelló, Ramon; A. Ramos, German
Abstract: In this work several architectures to implement repetitive controllers are compared. A complete analytical analysis is performed for these different architectures and a simulation example with a power converter is included.